Optimalisasi Sistem Informasi Layanan Jasa Konsultan dengan Metode Search Engine Optimization (SEO) - Hardianti Ramli; Indyah Hartami Santi; Rizki Dwi Romadhona (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
This study addresses the challenge of stagnant project acquisition faced by consulting service companies due to limited digital promotion. The purpose of this research is to design and implement a website optimized with Search Engine Optimization (SEO) to enhance the reach and competitive edge of CV Jaya Karya Konsultan. Employing a quantitative Research and Development (R&D) approach using the Rational Unified Process (RUP), the study involved developing key features including a company profile, project portfolio, client testimonials, educational blog, and chat box. The population comprised IT experts, internal company staff, and users, with purposive sampling yielding 33 respondents. Data were collected using observation, interviews, documentation, and questionnaires, and analyzed through descriptive statistics and thematic analysis. Research findings show the On-Page SEO strategy effectively improved website ranking, while technical and user experience results reached a usability rating of 91.43% ("very feasible"). In conclusion, developing a web-based information system using RUP and SEO strategies not only fulfills practical promotional needs but also offers a replicable model for service-sector digital transformation.